Indecent theology as catachrestic postcolonial method: Gayatri Spivak and Asian Catholic women - Peracullo, Jeane C. (Animo Repository, 2013)
This paper claims that despite diverse cultural frameworks Ecclesia of Women in Asia, a self-declared feminist theologian's group, use on issues surrounding body and sexuality in its book, Body and Sexuality: Theological-Pastoral Perspectives of Women in Asia (Quezon City: Ateneo de Manila Press, 2007), the articles in the book reflect a postcolonial methodology which fits into what Gayatri Spivak deems as catachresis which she defines as “the act of ‘reversing, displacing, and seizing the apparatus of value-coding.” Thus, indecent theology as a catachrestic term captures a particularly postcolonial methodology in the way EWA triangulates gender, religion and ethnicity to challenge women’s exclusion in the mainstream (masculinist) theologies as well as expose the implicit ethnocentricism in Western feminist theologies.